A target-oriented approach to neutrality in vowel harmony: Evidence from Hungarian - Avery Ozburn (Glossa, 2019)
This paper provides a novel perspective on neutrality in vowel harmony, using evidence from Hungarian. Despite the extensive study of Hungarian vowel harmony, the intermediate neutrality of [e:], which can alternate harmonically with [a:], is rarely addressed in existing analyses. While many standard accounts of harmony assume that front unrounded vowels like [e:] are neutral due to the lack of back counterpart, the [a:]~[e:] alternation makes this approach unsupportable. Specifically, since both [a:] and [e:] lack harmonic counterparts, but [a:] participates in harmony by re-pairing to [e:], the theory must explain why [e:] is not consistently harmonic. I argue that this pattern forces a new, target-focused approach, where participation is based on the vowel-specific drive to undergo harmony; neutrality results when this drive is insufficient to force unfaithfulness. This idea is motivated by cross-linguistic and phonetic facts suggesting that vowels that are low and/or rounded are inherently better targets of front/back harmony. I implement this approach formally in Harmonic Grammar; the harmony constraint is scaled by the quality of a vowel as a potential target, parallel to Kimper’s (2011) trigger strength scaling. This account can capture not only the basic Hungarian facts, but also the gradience of neutrality (the height effect) and the variability in Hungarian harmony. Moreover, I argue that this view of harmony is necessary beyond Hungarian and beyond front/back harmony: neutrality is crucially about the quality of a vowel as a potential target of harmony, where target quality is determined in a cross-linguistic, phonetically motivated way.